Culture Teaching Methods in Foreign Language Education: Pre-service Teachers’ Reported Beliefs and Practices - Maijala Minna (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
Culture teaching in a foreign language (FL) classroom involves linguistic and cultural knowledge about the target culture as well as pedagogical skills of integrating these into classroom practice. In general, more attention should be paid to culture teaching methods in FL teacher education in order to move from the traditional, teacher-centred approach towards a new dynamic and learner-centred practice. The main focus of this study is on Finnish pre-service FL teachers’ reflections and initial experiences in culture teaching during their one-year teacher education programme at a Finnish university. In 2012–2015, the data was collected through three questionnaires (N = 65) and interviews (N = 10) during consecutive one-year teacher education programmes. In the qualitative and quantitative analysis, we focused on trainees’ reflections on cultural content, methods, and initial culture teaching experiences. The main stumbling blocks in culture teaching emerging from this study were:  the integration of culture into the lessons, the use of the target language, and the use of personal cultural experiences in a pedagogically meaningful way. Based on the results of our study, we suggest that more reflection and work on culture teaching is required to meet the needs of teacher trainees. The results indicate that some development in Finnish pre-service FL teachers’ perception on culture could be observed, e.g. they wanted to promote interaction and share their personal cultural experiences with their students. Furthermore, recommendations for teacher educators regarding how to teach culture teaching, and how trainees could learn to integrate it into lessons are given.
Keywords: foreign language teaching and learning; pre-service language teacher cognition; culture teaching; language teacher education